Evaluation of shear wave dispersion in hepatic viscoelastic models including fibrous structure. (13th June 2019) - Fujii, Shiori; Yamakawa, Makoto; Kondo, Kengo; Namita, Takeshi; Shiina, Tsuyoshi
Abstract: In diagnosis of chronic hepatitis, shear wave elastography is utilized for the evaluation of fibrosis progression by estimating the viscoelasticity from shear wave speeds. The dispersion slope method is studied to evaluate the viscosity and fibrosis stage. However, when the shear wave length is a little larger than the size of fibrous structure in liver fibrosis tissues, shear wave propagates repeating reflection or refraction and influences the dispersion slope. We simulate shear wave propagation in a model with a fibrous structure and compare the dispersion slope with a homogeneous model in order to investigate the effect of the fibrous structure. As a result, the dispersion slope is dependent on the viscosity in a high frequency range but affected by the fibrous structure in a low frequency range. Results show that the fibrous structure influences contents of low frequencies. Using different frequency ranges to estimate the dispersion slope can help more precise viscoelasticity analysis.